2014
DOI: 10.2500/ajra.2014.28.4040
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Risk Factors and Comorbidities of Allergic Rhinitis in South Korea: The Fifth Korea National Health and Nutrition Examination Survey

Abstract: Prevalence, risk factors, and comorbidities of AR were evaluated in the general Korean population, which will contribute to prevention and treatment of AR and its comorbidities in Koreans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
63
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(67 citation statements)
references
References 38 publications
4
63
0
Order By: Relevance
“…Chronic obstructive pulmonary disorder (COPD) is one of the main causes of mortality in Korea 2. The prevalence of asthma, allergic rhinitis (AR), and rhinosinusitis is also increasing and has become the major health priority in Korea 3456. These preventable chronic respiratory diseases have a major adverse impact on quality of life, disability, and productivity, resulting in an increased socioeconomic burden.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic obstructive pulmonary disorder (COPD) is one of the main causes of mortality in Korea 2. The prevalence of asthma, allergic rhinitis (AR), and rhinosinusitis is also increasing and has become the major health priority in Korea 3456. These preventable chronic respiratory diseases have a major adverse impact on quality of life, disability, and productivity, resulting in an increased socioeconomic burden.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that the ARIA severity classification clearly discriminates among the impact of AR in all domains of quality of life and categorizes the symptom scores (Zicari et al, 2013). The duration and severity of AR are affected by numerous complex factors such as genetics, age, exposure time, exposure amount, and environmental factors Rhee et al, 2014;Portelli et al, 2015). Furthermore, large worldwide variations in the prevalence of AR symptoms have been explained based on these factors.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of allergic rhinitis (AR) in the general population is increasing and currently estimated to be approximately 10-25% 1,2. Although AR is not associated with a risk of death, the disorder can have a considerable effect on a patient's quality of life.…”
mentioning
confidence: 99%
“…Although AR is not associated with a risk of death, the disorder can have a considerable effect on a patient's quality of life. Consideration of comorbid diseases, including asthma, nasal polyp, olfactory dysfunction and chronic rhinosinusitis, results in a tremendous increase in the medical cost for AR treatment, which has come to entail more than just treating the rhinitis itself 1. Among the current treatment options for AR, specific allergen immunotherapy (SIT) is the only medical intervention that modifies fundamental immunologic mechanisms by inducing tolerance, and it can also modify the natural course of the disease.…”
mentioning
confidence: 99%